Efficacy of green tea mouth wash as an adjunct to non-surgical periodontal treatment in patients with chronic periodontitis - Sarwar Qasim Mustafa; Dilyar Ahmed Baban (Erbil Dental Journal)
Background and objectives: Periodontal disease is the most common disease associated with microbial infection with the destruction of supporting structures. This study was carried out to evaluate the effectiveness of green tea as a mouthwash in the management of chronic periodontitis in comparison to chlorhexidine mouthwash.